Formulation and Evaluation of Castor Oil (Ricinus communis L.) Lip Balm for Moisturizing Dry Lips - Nastiti, Ginanjar Putri; Muslikh, Faisal Akhmal; Maulina, Novia; Yusa, Queen; Ferliansyah, Diva Grace Putri; Jazila, Azra; Fitaloka, Gita S. (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2025)
Cosmetics today are not only used for beautification but also for maintaining health. One cosmetic product that has gained special attention is lip care cosmetics. Natural lip balms offer the significant advantage of minimal side effects. This study aims to design and evaluate a castor oil-based lip balm ( Ricinus communis L.) as a natural moisturizer. Three lip balm formulas were developed with varying concentrations of castor oil, cera alba, cera flava, and additional ingredients such as vaseline album, glycerin, propyl paraben, and BHT. The evaluation included organoleptic, homogeneity, and pH tests. The results showed that Formula II, containing 10% castor oil, delivered the best results, offering a softer, more moisturizing texture, an optimal maroon color, a strong grape essence aroma, and good homogeneity. Additionally, Formula II had a pH of 6.5, which aligns with the physiological pH of the lips. Based on these results, Formula II is considered the most effective and safe lip balm. This study highlights the great potential of castor oil in natural cosmetic formulations that provide protection and hydration for the lips.